Radiologic–pathologic discordance in biopsy-proven usual interstitial pneumonia - Yagihashi, Kunihiro; Huckleberry, Jason; Colby, Thomas V.; Tazelaar, Henry D.; Zach, Jordan; Sundaram, Baskaran; Pipavath, Sudhakar; Schwarz, Marvin I.; Lynch, David A. (The European respiratory journal, 2016)
The aim of this study was to compare the clinical, radiological and histological findings in a large population of subjects enrolled during a multicentre study of idiopathic pulmonary fibrosis, with a focus on discordance between imaging and histologic diagnoses of usual interstitial pneumonia (UIP). Two independent radiologists retrospectively reviewed 241 subjects who underwent high-resolution computed tomography (HRCT) and surgical lung biopsies. HRCT findings were classified as UIP, possible UIP and inconsistent with UIP. Histological findings were classified as definite, probable, possible and not UIP. Of the 241 cases, 102 (42.3%) had HRCT findings of UIP, 64 (26.6%) had possible UIP and 75 (31.1%) were inconsistent with UIP. Among those with UIP on HRCT, 99 (97.1%) had histologically definite or probable UIP (concordant group), and 71 (94.7%) of those with “inconsistent” HRCT features had histologically definite or probable UIP (discordant group). Discordant subjects were slightly younger and less likely to be smokers than concordant subjects, but no survival differences were identified. In this population of patients enrolled with a diagnosis of idiopathic pulmonary fibrosis, 94.7% of those with HRCT findings “inconsistent with UIP” demonstrated histological UIP. This suggests that the term “inconsistent with UIP” is misleading.